2015
DOI: 10.1007/s10212-015-0277-2
|View full text |Cite
|
Sign up to set email alerts
|

Declining trends in student performance in lower secondary education

Abstract: Student performance is related to motivation to learn. As motivation generally declines during lower secondary education, one might expect performance to decline as well during this period. Though, until now, it has been unclear whether this pattern exists. In the present study, we examined student performance during the early years of secondary education from a developmental perspective. Participants were 1544 Dutch secondary school students across three grades (grades 7 to 9). To investigate student performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 32 publications
2
31
2
1
Order By: Relevance
“…A report card grade for a specific subject is the average of multiple test scores a student has obtained throughout the school year. In a previous longitudinal study, we have shown that report card grade levels tend to decrease between the first and third year of secondary education (Wijsman, Warrens, Saab, Van Driel, & Westenberg, 2016). This means that, on average, students at the beginning of their secondary education start with higher report card grades than they have in their third year, while the standards are the same in all years.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…A report card grade for a specific subject is the average of multiple test scores a student has obtained throughout the school year. In a previous longitudinal study, we have shown that report card grade levels tend to decrease between the first and third year of secondary education (Wijsman, Warrens, Saab, Van Driel, & Westenberg, 2016). This means that, on average, students at the beginning of their secondary education start with higher report card grades than they have in their third year, while the standards are the same in all years.…”
Section: Methodsmentioning
confidence: 78%
“…Gender and school year (first or second) were also included in the study as control variables, as it has been demonstrated that these factors influence motivation and achievement levels (Wijsman et al, 2016), and the relationship between motivation and achievement (Freudenthaler, Spinath, & Neubauer, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Ο Πίνακας 3 παρουσιάζει τις παραγοντικές φορτίσεις που προέκυψαν καθώς και τους συντελεστές αξιοπιστίας εσωτερικής συνέπειας alpha. De Boer et al, 2013• Peetsma et al, 2005• Wijsman, et al, 2016• Wijsman et al, 2019.…”
Section: ερευνητικά εργαλείαunclassified
“…From T1 to T2 the dropout rate amounts 22.33% of participating students. The study focuses on this specific age group, as some studies indicate an achievement drop in school during this time period (Dohn, 1991;Wijsman et al, 2016). Initially, (1) written permission of the ethical committee of the Hoorn, Youth, and Sport (MBJS) of Brandenburg, (2) school consensus, and (3) both parents' and students' written and informed consensus was obtained.…”
Section: Participants and Proceduresmentioning
confidence: 99%